FENOMENOLOGI POLA KOMUNIKASI INTERPERSONAL PADA PASANGAN MENIKAH (STUDI LOVE LANGUAGE DALAM USIA PERNIKAHAN 0-5 TAHUN) - Luthfia Ramadhina Aulia (2022)
Marriage is a very important and sacred moment in one's life. The newly married couple are said to be enjoying romantic and exciting times. Within marriage, there is a pattern of daily interpersonal communication between married couples. In the communication of married couples, one of communication proponents when it comes to understanding the couple is Love Language. Love language is one of the ways or methods a person uses to express love for his or her spouse or family and those closest to them. The study aims to see how the patterns of interpersonal communication with the application of love language to married couples at 0-5 years of Marriage. The type of research used is qualitative descriptive with the phenomenological approach and use primary and secondary data sources. The analysis techniques in this study use interactive analysis.The sampling technique was carried out bt purposive sampling. The result of this study is that the application of love language to marriage at 0-5 years, can help a couple process of self-disclosure and a change in a better pattern of communication. It has also been found that the application of love language works in minimizing marital conflict or communication conflict.